Development of an Rt Nested PCR-Elisa Diagnostic Test for the Detection of Newcastle Disease Virus - Kho, Chiew Ling (1999)
Newcastle disease virus causes an economically important poultry disease known as Newcastle disease in Malaysia. The velogenic strain of this virus causes 1 00% mortality in infected chicken. Therefore, a rapid and sensitive diagnostic method is necessary for the detection of the virus. In this study a sensitive one tube reverse transcription nested PCR was developed by using two nested pairs of primer which were designed from the consensus fusion gene sequences. The outer primer sequences are 5'-T ACACCTCATCCCAGACAGGGTC-3' (FOP1) and 5'- AGGCAGGGGAAGTGATTTGTGGC-3' (FOP2). The inner primer pair with the sequence of 5'-T ACTTTGCTCACCCCCCTT-3' (FIP1) and 5'-CATCTTCCCAACTGCCACT-3' (FIP2) were labeled with biotin and digoxigenin at their 5' ends respectively. The PCR condition for the outer primers is 90°C/30 s, 67°C/30 s and 72°C/30 s for 20 cycles in which a 532 bp PCR product was generated. While for the inner primers, the PCR condition used is 90°C/30 s, 55°C/30 s and 72°C/15 s for a total of 30 cycles for the amplification of a labeled 280 bp PCR product. The primer pairs used are highly specific enabling the identification of all the three different pathotypes of NDV. No cross-reactions with other avian infectious agents such as infectious bronchitis virus, infectious bursal disease virus, influenza virus, and fowl pox virus were observed. The detection limit of this one tube nested peR technique was 3 pfu/ml of NDV by agarose gel electrophoresis detection method and was about 100 fold more sensitive compared to that of a non-nested RT - peR. To facilitate the detection of the peR product, the amplified peR product was then subjected to a colorimetric detection method using ELIS A where the labeled peR product was captured in a streptavidin coated microtiter plate and was detected by using anti-digoxigenin-peroxidase enzyme conjugate and 2,2'-azinodiethylbenzothiazolinesulfonic acid (ABTS) as the substrate. Comparisons between the detection methods of agarose gel electrophoresis and ELISA showed that the latter was 10-fold more sensitive than the former. The efficacy of the nested PCR-ELIS A was also compared with the conventional NDV detection method (HA test) and nonnested RT-PCR by testing against a total of 35 tissue specimens collected from NDsymptomatic chickens. With the cutoff value of 0.154 having been calculated from 15 known negative samples, 21 of 35 (60%) samples were tested to be NDV positive by nested peR-ELISA. One of these positive samples, however, was negative by nested peR and gel detection method. Only 8 of 35 (22.9%) samples were tested positive by non-nested RT-PCR and 2 of 35 (5.7%) samples were positive by the conventional HA test. Due to the high sensitivity of nested PCR-ELISA for the detection of NDV from tissue specimens, a peR-ELISA based diagnostic test may be a useful screening test especially in dealing with large number of samples.